Sea-Urchin-Inspired 3D Crumpled Graphene Balls Using Simultaneous Etching and Reduction Process for High-Density Capacitive Energy Storage - Lee, Jang Yeol; Lee, Kwang-Hoon; Kim, Young Jin; Ha, Jeong Sook; Lee, Sang-Soo; Son, Jeong Gon (WILEY-V C H VERLAG GMBH, 2015)
A crumpled configuration of graphene is desirable for preventing irreversible stacking between individual nanosheets, which can be a major hurdle toward its widespread application. Herein a sea-urchin-shaped template approach is introduced for fabricating highly crumpled graphene balls in bulk quantities with a simple process. Simultaneous chemical etching and reduction process of graphene oxide (GO)-encapsulated iron oxide particles results in dissolution of the core template with spiky morphology and conversion of the outer GO layers into reduced GO layers with increased hydrophobicity which remain in contact with the spiky surface of the template. After completely etching, the outer graphene layers are fully compressed into the crumpled form along with decrease in total volume by etching. The crumpled balls exhibit significantly larger surface area and good water-dispersion stability than those of stacked reduced GO or other crumple approaches, even though they also show comparable electrical conductivity. Furthermore, they are easily assembled into 3D macroporous networks without any binders through typical processes such as solvent casting or compression molding. The graphene networks with less pore volume still have the crumpled morphology without sacrificing the properties regardless of the assembly processes, producing a promising active electrode material with high gravimetric and volumetric energy density for capacitive energy storage.
Keywords: PSEUDOCUBIC ALPHA-FE2O3 PARTICLES; OXIDE NANOSHEETS; ACID; SUPERCAPACITORS; NANOCOMPOSITES; ARCHITECTURE; DISPERSIONS; ELECTRODES